1993
DOI: 10.1111/j.1600-051x.1993.tb00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal health of the population in eastern Germany (former GDR)

Abstract: The periodontal status of 1688 inhabitants of eastern Germany (former GDR) was investigated between July 1991 and March 1992, using the CPITN. The results show that only 1.4% of those examined have a healthy periodontal apparatus, whereas 40.1% had some signs of severe periodontitis (CPITN 4). This implies a very high therapy requirement in all age-groups, with 93.1% of 15- to 19-year-olds in need of peridontal treatment (CPITN 1 + 2 + 3 + 4). A comparison between educational qualifications and frequency of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…3). This finding is in agreement with Mengel et al (1993) and Hansen et al (1995) who reported that a low CPITN score was associated with a higher educational level.…”
Section: Discussionsupporting
confidence: 93%
“…3). This finding is in agreement with Mengel et al (1993) and Hansen et al (1995) who reported that a low CPITN score was associated with a higher educational level.…”
Section: Discussionsupporting
confidence: 93%
“…Of the independent variables considered in the present study, area of residence, as well as tooth brushing and flossing frequency were found to be the strongest determinants of periodontal diseases. These findings are consistent with those of other studies (Bourgeois et al, 1999;Marques, et al, 2000;Mengel et al, 1993). Given that the oral hygiene habits of the Greek seniors, as indicated from the present study, are far from been considered as satisfactory, improvement in oral hygiene practices should be an important public health issue.…”
Section: Clinical Parameterssupporting
confidence: 82%
“…To date, nationally representative and comprehensive data for Germany are lacking. Previously published studies did not provide sufficient information on prevalence and extent of periodontal diseases (Mengel et al 1993, Micheelis & Reich 1999). Only the regional Study of Health in Pomerania (SHIP) provided a comprehensive assessment of periodontal status in West Pomerania, a region in the very north east of Germany (Holtfreter et al 2009).…”
mentioning
confidence: 99%